Voluntary association in public goods experiments: Reciprocity, mimicry, and efficiency - Talbot Page; Louis Putterman; Bulent Unel (Brown University, Department of Economics, 2002)
We study the. Incentive effects of endogenous group formation in a voluntary contributon experiment. Subjects are given information on the past contributions of others and allowed to express a preference for partners. On the basis of the stated preferences new groups are formed. We find that the opportunity to form new groups increases both contributions and efficiency. also compare the regrouping mechanism with a mechanism allowing targeted reductions of others' earnings (,,punishmenf“). In the experiment; both mechanisms increase contribution levels significantly, but only endogenous grouping or the combination of the two increase efficiency significantly.
Keywords: C91; H41; D23; 330; Puhlic goods; Cüllective action; Group formation; and punishment; Öffentliches Gut; Gruppenentscheidung; Ökonomischer Anreiz; Test; Theorie